The connections between language and reading disabilities - Catts, Hugh W. (Hugh William), 1949-; Kamhi, Alan G., 1950- (L. Erlbaum Associates, 2005)
This is an edited book based on papers presented at a 2003 invitee-only conference under the sponsorship of the Merrill Advanced Studies Center of the University of Kansas. The participants were prominent scholars in the areas of language and reading, and have research programs funded by NIH and other sources.